Gunryu III: reconfigurable magnetic wall-climbing robot for decommissioning of nuclear reactor - Hirai, Masahiro; Hirose, Shigeo; Lee, Woosub (TAYLOR & FRANCIS LTD, 2013)
To perform the decommissioning on the inaccessible area to human workers, the need to develop a wall-climbing robot is increasing. In these wall-climbing robots, high mobility and stability on a surface of walls are most important required features. To achieve both of these features, the new type of arm-equipped reconfigurable multi-modules wall-climbing robot was proposed in this research. The stability and high mobility can be achieved by reconfiguration using attached arm as a connection mechanism. And the robot system composed of two mobile modules and 6DOF manipulator was developed as a proof mechanism. In this robot, for energy efficient and stable mobility at the environment of steel structure, the adsorption method based on magnet was selected and its functionality was confirmed. And, to enable intuitive control, the kinematic solver was developed and verified. Finally, basic experiment of motion test was performed, and it was confirmed that the proposed wall-climbing robot satisfies required functions, such as high mobility and stability.